Assessment of the Ocloro River’s environmental health, using a mixed methodology - Chaves-Villalobos, María (2023)
The sustainability of urban areas nowadays faces significant challenges, due to high levels of pollution caused by population density. Therefore, the availability of water resources appears to be becoming increasingly compromised, as a result of inappropriate management of the solid and liquid waste generated by different human activities. The Ocloro River is a clear example of this problem, as evidenced by the deterioration of its environmental health. A mixed methodology was used to know about it, the first method was to characterize water quality using physicochemical and microbiological parameters, later on, the determination of the Duch index, giving a total of 16 samples of class 5 “extreme contamination” and 4 samples of class 4 “severe contamination”, from 2019 to 2021. In the second stage, a perception survey was conducted among a specific sector of the Barrio Luján population, approaching information from 80 homes, where 54 people indicated that the river pollution had affected them; additionally, the majority rated the level of pollution as 8, where 10 was the value with the highest level of pollution. Finally, the POSH method was used, which allowed the identification of some of the main point sources of pollution near the river, determining 27.1 % of high pollution, 22.3 % of moderate pollution, and 50,6 % of reduced pollution; this last one corresponds to the northern part of the river micro-basin in the communities of San Pedro, Los Yoses, and Francisco Peralta.